Dental education development reflection from an objective structured clinical examination - Stanley Shih-Li Tsai; Jenny I-Chun Sar; Jenny Zwei-Chieng Chang; Szu-Hsien Yu; Eddie Hsiang-Hua Lai; Chun-Pin Lin (Elsevier, 2015)
Background/purpose: Recently, dental education has put emphasis on the assessment of clinical competencies using an objective structured clinical examination (OSCE). The purpose of this study was to assess several clinical competencies required for dental graduates by having dental students and residents of different levels take the same set of OSCEs. Materials and methods: Twelve 5th-grade dental students (D5), 12 dental interns (Ri), and 12 1st-year dental residents (R1) were recruited to take the same set of OSCEs composed of six stations: Station 1, explanation of a treatment plan for restoration of a missing tooth; Station 2, taking a study cast impression with alginate; Station 3, explanation of a treatment plan for restoration of an inlay; Station 4, explanation to a mother for taking a radiograph of her child's tooth; Station 5, placement of a rubber dam on a designated tooth and Station 6, explanation of pulpitis diagnosis and treatment. The examinee's performance was graded using both global rating and checklist scores. Results: There were significant differences in the mean global rating and checklist scores of Stations 3, 5, and 6 among the three groups. In Stations 3 and 5, Ri performed best, followed by R1 and D5. In Station 6, R1 performed best, followed by Ri and D5. In Stations 1, 2, and 4, there were no significant differences among the three groups. However, Ri performed better than R1 in Station 1. Conclusion: More emphasis should be placed on professional communication skills in the resident training program.